2013
DOI: 10.1371/journal.pone.0079370
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD4+CD161+ T Lymphocytes Are Increased in Seropositive Arthralgia Patients but Decreased in Patients with Newly Diagnosed Rheumatoid Arthritis

Abstract: Improved understanding of the immune events discriminating between seropositive arthralgia and clinical synovitis is of key importance in rheumatology research. Ample evidence suggests a role for Th17 cells in rheumatoid arthritis. We hypothesized that CD4+CD161+ cells representing Th17 lineage cells may be modulated prior to or after development of clinical synovitis. Therefore, in a cross-sectional study, we investigated the occurrence of CD4+CD161+ T-cells in seropositive arthralgia patients who are at risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 37 publications
4
39
1
Order By: Relevance
“…Rather, the Fr III subset tended to decrease in RA patients compared to SAP. The latter is in line with previous work from our group indicating that peripheral CD4+CD161+ T cells (Th17 lineage cells) are increased in SAP, but decreased in RA patients at disease onset with an enrichment of these cells in the joints [ 28 ]. The tendency that peripheral Fr III numbers are lower at inclusion in switched SAP compared to non-switched SAP might indicate that Th17-cells migrate to inflammatory sites in the joints, although an earlier immunohistochemical study could not detect an increase of T-cells in synovial biopsies from SAP who later developed RA compared to HC [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Rather, the Fr III subset tended to decrease in RA patients compared to SAP. The latter is in line with previous work from our group indicating that peripheral CD4+CD161+ T cells (Th17 lineage cells) are increased in SAP, but decreased in RA patients at disease onset with an enrichment of these cells in the joints [ 28 ]. The tendency that peripheral Fr III numbers are lower at inclusion in switched SAP compared to non-switched SAP might indicate that Th17-cells migrate to inflammatory sites in the joints, although an earlier immunohistochemical study could not detect an increase of T-cells in synovial biopsies from SAP who later developed RA compared to HC [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…The ratio of IFNγ+Th17 cells in memory T cells was inversely correlated to the titers of anti-CCP antibodies. It has been reported that cell populations in synovial tissues may shift inversely to those in peripheral blood in RA [ 13 ]. Thus, we speculated that IFNγ+Th17 cells are infiltrated in synovial tissue with inflammation in RA patients with high titers of ACPA with decreased peripheral ratio of IFNγ+Th17.…”
Section: Th17-producing Ifnγ (Ifnγ+ Th17)mentioning
confidence: 99%
“…In addition, the levels of IL-17 in individuals before RA onset is significantly higher than that in patients after RA onset [ 12 ]. In 2013, Chalan et al reported that the number of circulating CD4+CD161+T lymphocytes are elevated in seropositive arthralgia before the onset of RA but decreased in patients with newly diagnosed RA [ 13 ]. In contrast, a regulatory variant in CC chemokine receptor 6 (CCR6, a specific marker for Th17 cells [ 14 , 15 ]) is related to RA susceptibility [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Maggi et al provided evidence that CD161 is a marker of all human IL-17-producing T cell subsets, including CD3+CD4+CD8−, CD3+CD4−CD8+, and CD3+CD4−CD8− cells [ 14 ]. It has been reported that circulating CD4+CD161+ T cells are increased in seropositive arthralgia patients but decreased in newly diagnosed RA patients [ 15 ]. Furthermore, this study showed that CD4+CD161+ T cells were enriched in synovial fluid (SF), while CD8+CD161+ T cells were not accumulated in SF of RA patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that circulating CD4+CD161+ T cells are increased in seropositive arthralgia patients but decreased in newly diagnosed RA patients [ 15 ]. Furthermore, this study showed that CD4+CD161+ T cells were enriched in synovial fluid (SF), while CD8+CD161+ T cells were not accumulated in SF of RA patients [ 15 ]. In fact, we have previously demonstrated that RA patients seemed to have higher percentages of circulating CD161+ cells in CD4+ T cells than healthy controls, but the difference did not reach statistical significance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%